Twenty-five years of RENHIS: a history of histopathological studies within EUVAS - Daalen, Emma; Ferrario, Franco F.; Noël, Laure-Hélène; Waldherr, Rüdiger; Hagen, E. Christiaan; Bruijn, Jan A.; Bajema, Ingeborg M. (Nephrology, dialysis, transplantation, 2015)
Abstract. In the early 1990s, an international working group of experienced renal pathologists, the Renal Histology group, set up a scoring system for biopsies